Study on the Addition of A Swirling Vane to Spark Ignition Engines Fueled by Gasoline and Gasoline-Ethanol - Wawan Purwanto; Jerry Chih Tsong Su; Muhammad Latifur Rochman; Budi Waluyo; Krismadinata Krismadinata; Ahmad Arif (Universitas Muhammadiyah Magelang, 2023)
Although the technology of fuel injection in motorcycles has reached ports and direct injection, motorcycles with carburetors are still used. In this research, the carburetor was modified by adding a swirling vane. This study is intended to provide an explanation regarding engine performance which includes torque, power, mileage, emissions, and engine oil temperature. The study begins with a review of the shape and flow characteristics of the swirling vane based on the largest flow according to previous studies. Then, a swirling vane is built and tested to ensure its optimal shape. The findings were compared with conventional carburetor-based engines that had not been treated. Experiments were also carried out on gasoline-ethanol to obtain optimal results and use them appropriately for alternative fuel applications. A comparison of data on torque, power, exhaust emissions, temperature, and mileage reveals that vehicles modified with swirling vanes have better performance. Furthermore, based on the results of gasoline-ethanol application tests, this design is only suitable for use up to E25.